Pemberdayaan Komunitas Sahabat UMKM NTB Melalui Workshop Pembuatan P.T Perseorangan di Kota Mataram - Putra, Eduard Awang Maha; Mandala, Opan Satria; Prayuda, Hilman; Alfurqan, Imam; Renda, Rapi (CV. Global Cendekia Inti, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are critical to driving economic growth, particularly by creating jobs, increasing household incomes, and reducing poverty. In Nusa Tenggara Barat (NTB), 786 registered MSMEs operate across various sectors such as trade, agriculture, and industry. However, many MSMEs face challenges due to a lack of legal business status, which limits their access to financing, market opportunities, and consumer trust. To address this issue, the Sahabat UMKM NTB Community, in collaboration with the government, organized a workshop focused on establishing Individual Limited Companies (PT Perseorangan). This initiative aimed to raise awareness about the importance of business legality, provide technical guidance on registration procedures, and offer hands-on assistance in obtaining legal business status. The program utilized socialization sessions, practical training, and continuous mentorship to support MSME actors in navigating the registration process via the DJAHU system. As a result, several MSMEs successfully obtained legal status, improving their credibility, access to financing, and market reach. This program underscores the significance of collaborative efforts between government, local communities, and technology in empowering MSMEs, enabling them to contribute more effectively to regional and national economic development.